Determinants of the Long-Term Performance of Malaysian Initial Public Offerings - Shari, Wahidah; Abu Hassan, Mohamad Hanif (Universiti Utara Malaysia Press, 2024)
This study examined the determinants of the long-term performance of 351 initial public offerings (IPOs) launched in Malaysia over the 2002–2010 period. This paper used a panel regression analysis framework based on the ordinary least squares (OLS) technique to examine the potential determinants of IPOs’ long-term performance. The findings revealed that the volatility of aftermarket returns, the dummy ACE market and concentration ownership significantly influence the long-term performance of Malaysian IPOs. This paper offers important implications specifically for investors as the findings can help them understand more about public companies’ long-term performance and how to better predict their performance